Transcriptome-Wide Identification of Preferentially Expressed Genes in the Hypothalamus and Pituitary Gland - St-Amand, Jonny; Yoshioka, Mayumi; Tanaka, Keitaro; Nishida, Yuichiro (Frontiers in Endocrinology, 2012)
To identify preferentially expressed genes in the central endocrine organs of the hypothalamus and pituitary gland, we generated transcriptome-wide mRNA profiles of the mouse hypothalamus, pituitary gland and parietal cortex using serial analysis of gene expression (SAGE). Total counts of SAGE tags for the hypothalamus, pituitary gland and parietal cortex were 165824, 126688 and 161045 tags, respectively. This represented 59244, 45151 and 55131 distinct tags, respectively. Comparison of these mRNA profiles revealed that 22 mRNA species, including three potential novel transcripts, were preferentially expressed in the hypothalamus. In addition to well-known hypothalamic transcripts, such as hypocretin, several genes involved in hormone function, intracellular transduction, metabolism, protein transport, steroidogenesis, extracellular matrix and brain disease were identified as preferentially expressed hypothalamic transcripts. In the pituitary gland, 106 mRNA species, including 60 potential novel transcripts, were preferentially expressed. In addition to well-known pituitary genes, such as growth hormone and thyroid stimulating hormone beta, a number of genes classified to function in transport, amino acid metabolism, intracellular transduction, cell adhesion, disulfide bond formation, stress response, transcription, protein synthesis and turnover, cell differentiation, the cell cycle and in the cytoskeleton and extracellular matrix were also preferentially expressed. In conclusion, the current study identified not only well-known hypothalamic and pituitary transcripts but also a number of new candidates likely to be involved in endocrine homeostatic systems regulated by the hypothalamus and pituitary gland.